The Routledge handbook of gender and violence - Lombard, Nancy (Routledge handbooks, 2018)
The Routledge Handbook of Gender and Violence provides both a comprehensive and authoritative state-of-the-art overview of the latest research in the field of gender and violence. Each of the 23 specially commissioned chapters develops and summarises their key issue or debate including rape, stalking, online harassment, domestic abuse, FGM, trafficking and prostitution in relation to gender and violence. They study violence against women, but also look at male victims and perpetrators as well as gay, lesbian and transgender violence. The interdisciplinary nature of the subject area is highlighted, with authors spanning criminology, social policy, sociology, geography, health, media and law, alongside activists and members of statutory and third sector organisations. The diversity of perspectives all highlight that gendered violence is both an age-old and continuing social problem. By drawing together leading scholars this handbook provides an up-to-the-minute snapshot of current scholarship as well as signposting several fruitful avenues for future research. This book is both an invaluable resource for scholars and an indispensable teaching tool for use in the classroom and will be os interest to students, academics, social workers and other professionals working to end gender-based violence.
Keywords: approches et analyses; communication; cours; criminologie; discipline; droit; géographie; justice sociale; outils; ouvrages de références; premier cycle; rapports sociaux de sexe; ressource en ligne; santé; science politique et droit; sciences humaines; sex1911; sexualité; sociologie; sofia; thématiques; travail; violences

Geography and gender: Feminism and a feeling of justice - Wright, Melissa W. (Progress in Human Geography, 2010)
The recent emphasis on emotional geographies has turned critical attention to the connections linking affect and social justice. It is hard to imagine this ‘emotional turn’ in the field without much of the ground having been laid by feminist challenges to epistemology, objectivity, rationality, to the gendering of knowledge and the conceptualization of human embodiment, psychic life, subjectivity, and political agency, all in relation to power so often substantiated around a belief that the public and the private are discrete and oppositional domains necessary for organizing social, economic, and political life. In this report, I address the following questions. How can feminist and emotional geography tighten their connections, fuel their shared passions and generate a synergy of scholarship oriented toward activism and progressive change? How can geographies of feeling broaden the path for justice that feminism endeavors to plow? In doing so, I continue my emphasis on research that grounds theoretical discussion with research conducted in activist projects conducted in the name of social justice. I do so as a matter of my own emotional investments – I firmly believe that scholarship must engage with the ways in which people beyond the academy wrestle with the concepts in their daily lives that scholars contemplate, sharpen, and circulate through academic production. So the debates that we scholars so often have with ourselves over the finer points of theory reveal, in my view, their greater significance when they provide tools useful for people who seek to create kinder and more compassionate worlds. Thus, I highlight the scholarship that creates toolkits out of feminist scholarship, emotional geographies, and research on social justice.
Keywords: approches et analyses; care; discipline; genre; géographie; justice sociale; militance; ressource en ligne; sciences humaines; thématiques; travail; travail du care; émotions